CHINA'S PUBLIC SECURITY POLICY: CONTROL, STABILITY AND EVOLUTION COMPARED TO BRAZIL - Bispo dos Santos, Fábio (Revista Gênero e Interdisciplinaridade, 2025)
This article aims to analyze China’s public security policy, taking into account its foundations, main components, and historical evolution. In addition, the article establishes a comparison with Brazil’s public security policy, highlighting similarities and differences in their approaches and challenges. China’s public security policy is characterized by the prioritization of social stability, the leadership of the Chinese Communist Party (CCP), and the use of a combination of methods, including repressive measures and technological surveillance. Meanwhile, Brazil faces its own complex challenges, including high crime rates and the need to balance security with human rights.